2004
DOI: 10.1023/b:qure.0000037499.80080.07
|View full text |Cite
|
Sign up to set email alerts
|

Order effects in the assessment of quality of life in cancer patients

Abstract: Methodological studies and outcome research often include several health-related quality of life (HRQoL) measurement scales in one questionnaire. Psychological studies have previously demonstrated that changing the sequential order of measurement scales within a questionnaire can alter the pattern of responses. Little is known, however, about whether there are order effects on the assessment of HRQoL in cancer patients. Here we address this issue in a study of 190 Singaporean cancer patients who were assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
35
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 8 publications
3
35
0
Order By: Relevance
“…However, recent studies suggested that the context of HRQoL assessment has little effect on HRQoL scores (Kemmler et al, 1999;Cheung et al, 2004b). Furthermore, a comparison of the findings of the Chinese Quick-FLIC in this study with our previous study, where the 11 items Quick-FLIC was administered as an independent instrument showed similar results.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…However, recent studies suggested that the context of HRQoL assessment has little effect on HRQoL scores (Kemmler et al, 1999;Cheung et al, 2004b). Furthermore, a comparison of the findings of the Chinese Quick-FLIC in this study with our previous study, where the 11 items Quick-FLIC was administered as an independent instrument showed similar results.…”
Section: Discussionsupporting
confidence: 76%
“…One challenge may be that the validity and reliability of these 11 items administered as part of the FLIC could have been affected by the other FLIC items. However, recent studies suggested little context effect in quality of life assessment (Kemmler et al, 1999;Cheung et al, 2004b). Furthermore, we also used the same 11 items in Chinese to re-evaluate the Chinese version of Quick-FLIC.…”
mentioning
confidence: 99%
“…Order was not specified, so it is unlikely that instruments were administered in the same order across study sites and time periods. Order effects are found more often in large population-based surveys of predominantly healthy individuals than in surveys of smaller samples of the chronically ill [74][75][76]. This may reflect limited power to detect small effects.…”
Section: Discussionmentioning
confidence: 72%
“…One of the two surveys used PDQ-8 alone, whereas the other administered the eight items embedded in the PQD-39. However, various studies have shown that there is little context effect in the qualityof-life assessment [27,28], so we believed that the data from the two surveys can be pooled. We also used the present data to explore the possibility of a context effect.…”
Section: Discussionmentioning
confidence: 99%